Editorial Footprints - Escobar, John Willmer (Cuadernos de Administración, 2024)
Significant changes have occurred in the Cuadernos de Administración journal over the past three years, including the ongoing publication of articles, the elimination of publication calls for each volume, the introduction of a new session in the journal for "forthcoming papers," improvements in the quality of English of the texts, and the organization of processes and standards to meet indexing requirements in databases such as Scopus, among others. These positive changes have positioned the journal Cuadernos de Administración at the Universidad del Valle as a nationally and internationally recognized platform for disseminating research in the field of Administrative Sciences in Latin America.All these changes have been greatly aided by the editorial team of Cuadernos de Administración. Therefore, it is necessary to express gratitude and highlight the support Alma Victoria Parra Franz and the editorial team members under her guidance have given over these three years, without whom none of the achievements would have been possible.A new path is beginning for the journal, with new indexing goals and accomplishments to be achieved in the coming years. I am confident that the journal will continue to thrive under the leadership of the new Editor-in-Chief. I am grateful for the trust the Dean's Office of the Faculty of Administrative Sciences placed in me for my appointment as Editor-in-Chief during this period, and I wish the greatest success to my successor. For now, I will support the journal's development from the direction of the Editorial Program.